Analysis Of E-Service Quality Factors That Affect E-Satisfaction - Dayan Hakim Natigor Sipahutar; Irdawati, Desthy Anggrainy Ramdhani (Dinasti International Journal of Management Science, 2024)
One of the fintech applications in the field of different bank fund transfer services for free is the Flip application. There were 59% positive comments which meant that customers felt that the Flip fintech application provided satisfaction with their use, and there were 41% negative comments that some of the obstacles experienced by users were usually related to tangibles, reliability, responsiveness, empathy and assurance. This study aims to determine the effect of the dimensions of E-service Quality on E-satisfaction. The results of the respondents who received as many as 100 respondents. Data processing using SPSS v26 software. The results of the descriptive research show 1) E-satisfaction is in the good category. 2) Tangibles are in the good category. 3) Reliability is in very good category. 4) Responsiveness is in the very good category. 5) Empathy is in the very good category. 6) Assurance is in the good category. 7) Tangibles with e-satisfaction have a very weak correlation, the determination value is 3.3% and Tangibles have no effect on e-satisfaction. 8) Reliability with e-satisfaction has a weak correlation, determination value is 8.6% and Reliability has no effect on e-satisfaction. 9) Responsiveness with e-satisfaction has a weak correlation, determination value is 10.6% and Responsiveness has no effect on e-satisfaction. 10) Respondents' empathy for e-satisfaction has a weak correlation, the determination value is 5.9% and empathy has no effect on e-satisfaction. 11) Assurance with e-satisfaction has a moderate correlation, the determination value is 16.9% and Assurance has an effect on e-satisfaction. 12) Simultaneously the e-service quality variables, namely tangibles, reliability, responsiveness, empathy, and assurance, have a positive and significant influence on e-satisfaction.